DIFFERENTIAL ANALYSIS OF GENE RELATED TO HARD BUNCH PHENOMENA IN OIL PALM (ELAEIS GUINEENSIS JACQ) FRUITS - Roberdi, Roberdi; Sobir, Sobir; Yahya, Sudirman; Toruan-Mathius, Nurita (Emirates Journal of Food and Agriculture, 2015)
Identification of differentially expressed genes can be done by cDNA-AFLP analysis. Hard bunch phenomena are not widely studied. The aim of this research was to identify and characterize regions specific to the gene coding sequences involved in the hard bunch phenomena in oil palm fruits. RNA was isolated from three types of ripe oil palm fruits including normal, black and hard bunch fruits. cDNAs were amplified using 16 AFLP primer pairs combinations. The result of a BLAST comparison showed that some of the resulting transcripts have sequence similarity with the existing database sequences, such as a WRKY transcription factor, peroxidase, actin depolymerising factor and glutamine synthetase allegedly associated with hard bunch phenomenon induced by drought stress. However, some transcripts could not be classified since they did not exhibit significant similarity to any existing database sequences. This is might be the transcripts were less conserve region and or 5’ or 3’ UTR region.